Development of the Trust's programme of scientific research - Matthews, G V T (Wildfowl, 1956)
While all aspects of the biology of the Anatidae come within our purview, those having a bearing on the conservation of the group have always had priority. It is very satisfactory to report that the Nature Conservancy have shown their recognition of the value of the work being done by making increasingly substantial grants towards the cost of the programme. These will not only enable lines of research already in being to be continued at an increasing tempo, but allow new lines to be developed. Thus we have embarked on an investigation of the use of aerial survey methods under British conditions.